Efektivitas Strategi PBL Berbasis Potensi Akademik Terhadap Keterampilan Pemecahan Masalah dan Berpikir Kritis Siswa SMA Pada Topik Lingkungan - I Wayan Karmana; Iwan Dody Dharmawibawa; Titi Laily Hajiriah (Lembaga Penelitian dan Pendidikan Mandala, 2020)
The purpose of this research is to explain the effect of Problem Based Learning (PBL) and academic potential and their interactions toward problem solving and critical thinking skills of high school students. This research is a quasi-experiment that implements two different strategies with pretest-posttest non equivalent control group design by treatment factorial 2x2 which was conducted in the 2018/2019 academic year. Population of this research was class X students of SMA Negeri 8 Mataram, while the research sample was class X students of 2 classes with a purposive sampling technique. Research instruments is test of problem solving skills and test of critical thinking skills. Data analysis was performed with descriptive analysis and to test the hypothesis an anacova test was followed by further test used of Least Significant Difference (LSD). The calculation is aided by the SPSS 14 for Windows program. The results of this research showed that Problem Based Learning affects the problem solving and critical thinking skills. While academic ability (potential) and interaction of learning strategies with academic potential do not affect the problem solving and critical thinking skills of high school students on enviromental topic.